GEOPOLITICAL POSITION OF SERBIA AFTER THE BEGINNING OF THE WAR IN UKRAINE: NEUTRALITY AND STRATEGIC DETERRENCE IN A CRISIS CONTEXT - Gajic, Aleksandar (Serbian political thought, 2023)
The Paper examines the contemporary geopolitical position of the Republic of Serbia after the beginning of the war in Ukraine, with the aim of confirming the hypothesis that even in the new, difficult geopolitical conditions, it is possible to maintain the current policy of military neutrality and increase its own capacities for strategic deterrence. Starting with the geopolitical position of Ukraine in the Eurasian space, the strategies and goals of “Great Powers” in this conflict and the importance that Russia’s current military confrontation with the "collective West" is taking in it, the first part of the Paper examines the influence of crisis in East Europe and on Serbia’s foreign policy strategy (which, before the beginning of conflict, was moving between neutrality and the "hedging strategy”). Therefore, first part of the Paper gives brief theoretical overlook on foreign policy strategies of small states and their conditioning by geopolitical factor, primarily geopolitical position. With all that taken into consideration, it is easier to have clear overview of Serbia`s current geopolitical position and dilemmas. The second part of the Paper is dedicated to the description of Serbia’s contemporary difficult position in the new geopolitical circumstances ("lonely and in the encirclement"), in order to better understand both the numerous challenges to which Serbia is exposed and its foreign policy moves aimed at preserving its military neutrality and the ability for strategic deterrence. On the one hand, Serbia wants to keep up its processes of accession to the EU and to continue to develop the best possible relations with the West and not to confront it and be isolated. On the other hand, Serbia wants to maintain existing relations with the Russian Federation which are of vital interest to Serbia because, as a permanent member of the UN Security Council, Russia is able to prevent the accession of Kosovo and Metohija, the breakaway southern Serbian province, to the United Nations as an independent state. Serbia also wants to preserve the current supply of cheap energy resources for its internal needs from the Russian Federation, because it has no real alternative for them. While remaining military neutral, Serbia also needs to increase its deterrence capabilites: the tightening of relations with certain neighbors increases not only the conflict potential, that is, the possible threat of the use of force, but also requires approaches of using "extended deterrence" with a necessary increase in independent forms of hard, military power, that is, additional investment in increasing one’s own combat capacities, which would achieve the maximum achievable deterrence effect. The final considerations in the Paper refer to the geopolitical perspectives of persistence in neutrality, that is, to the confirmation of the basic hypothesis of the Paper on the sustainability of this policy in difficult circumstances.